Acoustic change responses to amplitude modulation: a method to quantify cortical temporal processing and hemispheric asymmetry - Han, Ji Hye; Dimitrijevic, Andrew (Frontiers in Neuroscience, 2015)
Objective: Sound modulation is a critical temporal cue for the perception of speech and environmental sounds. To examine auditory cortical responses to sound modulation, we developed an acoustic change stimulus involving amplitude modulation (AM) of ongoing noise. The AM transitions in this stimulus evoked an acoustic change complex (ACC) that was examined parametrically in terms of rate and depth of modulation and hemispheric symmetry. Methods: Auditory cortical potentials were recorded from 64 scalp electrodes during passive listening in two conditions: (1) ACC from white noise to 4, 40, 300 Hz AM, with varying AM depths of 100, 50, 25% lasting one second and (2) one second AM noise bursts at the same modulation rate. Behavioral measures included AM detection from an attend ACC condition and AM depth thresholds (i.e., a temporal modulation transfer function, TMTF). Results: The N1 response of the ACC was large to 4 and 40 Hz and small to the 300 Hz AM. In contrast, the opposite pattern was observed with bursts of AM showing larger responses with increases in AM rate. Brain source modeling showed significant hemispheric asymmetry such that 4 and 40 Hz ACC responses were dominated by right and left hemispheres respectively. Conclusion: N1 responses to the ACC resembled a low pass filter shape similar to a behavioral TMTF. In the ACC paradigm, the only stimulus parameter that changes is AM and therefore the N1 response provides an index for this AM change. In contrast, an AM burst stimulus contains both AM and level changes and is likely dominated by the rise time of the stimulus. The hemispheric differences are consistent with the asymmetric sampling in time hypothesis suggesting that the different hemispheres preferentially sample acoustic time across different time windows. Significance: The ACC provides a novel approach to studying temporal processing at the level of cortex and provides further evidence of hemispheric specialization for fast and slow stimuli.